Learning OpenStack : set up and maintain your own cloud-based infrastructure as a service (IaaS) using OpenStack /: set up and maintain your own cloud-based infrastructure as a service (IaaS) using OpenStack. (2015) - Shrivastwa, Alok; Sarat, Sunil
No abstract available